Geometric Effects of an Inhomogeneous Sea Ice Cover on the under Ice Light Field - Katlein, Christian; Perovich, Donald K.; Nicolaus, Marcel (Frontiers in Earth Science, 2016)
Light measurements in the ocean provide crucial information about the energy fluxes in the climate and ecosystem. Currently radiative transfer problems are usually considered in horizontally homogeneous layers although it is known to be a crude assumption in many cases. In this paper, we examine the effects of a horizontally inhomogeneous sea ice layer on the light field in the water underneath. We implemented a three dimensional model, capable to simulate the light field underneath arbitrary surface geometries using ray optics. The results show clear effects of the measurement geometry on measured fluxes obtained with different sensor types, which need to be taken into account for the correct interpretation of the data. Radiance sensors are able to better sense the spatial variability of ice optical properties as compared to irradiance sensors. Furthermore we show that the determination of the light extinction coefficient of water from vertical profiles is complicated under a horizontally inhomogeneous ice cover. This uncertainty in optical properties of the water, as well as the measurement geometry also limits the possibility to correct light measurements taken at depth for the influence of water in between the sea ice and the sensor.